Examining Barriers to Practice in Genitourinary and Gynecologic Radiation Oncology: Results from 2 Nationwide Surveys - Patrick Doyle, MS; Neha Vapiwala, MD, FACR, FASTRO, FASCO; Mutlay Sayan, MD; Miranda Lam, MD, MBA; Shalini Moningi, MD (Advances in Radiation Oncology)
Purpose: Gender diversity in academic radiation oncology (RO) has become a topic of interest in recent years, with studies showing that practicing female academic radiation oncologists (AROs) are outnumbered by male colleagues at a rate of approximately 3:1. Gender differences are also observed in subspecialties whose patient populations are overwhelmingly of a single gender, such as genitourinary (GU) and gynecologic (GYN) RO. We aimed to investigate whether challenges exist for academic RO physicians who primarily treat patients of another gender, and, if so, what barriers they face in practice. Methods and Materials: We conducted 2 national surveys of female GU academic RO physicians and male GYN academic RO physicians working at Accreditation Council for Graduate Medical Education-accredited academic centers. Survey questions focused on career path, challenges faced, and barriers to practicing GU or GYN oncology. Results: A total of 13/42 (30.2%) GU survey recipients responded as treating GU oncology and 31/77 (40.3%) GYN survey recipients responded as treating GYN oncology. Of these respondents, 9 GU and 3 GYN physicians reported facing challenges as an academic RO faculty member because of their gender identity, and 5 GU and 4 GYN physicians reported that their subspecialty specifically presented challenges. Neither group commonly reported difficulties developing trust and rapport with patients. In the GU academic RO group, reports of challenging relationships with other professional colleagues were common. Difficulties finding or serving as a mentor were also common in both groups. Conclusions: Female GU AROs and male GYN AROs may face unique challenges. Identifying and understanding these challenges directly from practicing physicians are important steps in improving professional success, career satisfaction, and clinical care quality.